2015
DOI: 10.15713/ins.jcri.35
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sexual dimorphism by using permanent maxillary first molar in Gujarati population

Abstract: Background: Sexual dimorphism refers to those differences in size, stature and appearance between male and female that can be applied to dental identification of humans. Teeth are good sources of material for civil and medico-legal identification. Tooth size standards based on odontometric investigation can be used in age and sex determination. The present study was planned to evaluate the existence of sexual dimorphism using both buccolingual (BL) and mesiodistal (MD) dimensions and prevalence of cusp of Cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The present study presents data on buccolingual and mesiodistal widths and so forth both maxillary FM and SM molars concerning the Urhobo. The observation on the relative dimensions of the buccolingual and mesiodistal widths was in tandem with previous studies [91213141920]. It was also consistent with Sharma et al [11] in the case of maxillary SM; but on the contrary, it was at variance with the latter in the case of maxillary FM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study presents data on buccolingual and mesiodistal widths and so forth both maxillary FM and SM molars concerning the Urhobo. The observation on the relative dimensions of the buccolingual and mesiodistal widths was in tandem with previous studies [91213141920]. It was also consistent with Sharma et al [11] in the case of maxillary SM; but on the contrary, it was at variance with the latter in the case of maxillary FM.…”
Section: Discussionsupporting
confidence: 91%
“…In a related study in India, Banerjee [8] reported statistically significant differences between the sexes in mesiodistal and buccolingual widths of maxillary FM. Also in India, in Gujarati population, Bhavasar et al [20] reported that the right mesiodistal and left mesiodistal widths were statistically significantly higher in males compared to females, in contrast to the right and left bucculingual widths. The higher dentine in the crown of male teeth compared to female, as has been pointed out in the aforementioned studies could be the reason for the dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study conducted by Lakhanpal et.al [16] on study models to assess the gender predictability of various maxillary tooth and concluded that the MD width of maxillary 1 st molars has the most significant value and the mean value of males were higher than females. Rashmi et.al [17] concluded that a significant difference in the mean values between males and females of Guajarati population was noted suggesting that this parameter could be used in gender assessment. The dissimilarity in the results could be explained by a variety of factors which are involved in making the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Sexual dimorphism refers to those differences in size, stature, and appearance between male and female that can be applied to dental identification as no two mouths are alike. [6,7] Gender dimorphism in tooth size has been demonstrated by anthropologists and odontologists in bucco-lingual and mesio-distal dimensions of teeth (linear dimensions). [ 1,8,9,10] and diagonal measurements of tooth crowns.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] The tooth size variations are influenced by both genetic and environmental factors. [6] Many studies established that permanent mandibular canines exhibit greater sexual dimorphism but permanent maxillary first molars erupt early in the oral cavity at the mean age of 6-7 years and are less commonly impacted when compared to canines. [7] The odontometric features of permanent maxillary first molars that erupt at an early age can be of immense use in gender determination.…”
Section: Introductionmentioning
confidence: 99%